Relationship among body condition, subcutaneous fat and production performance of Jersey crossbred cows - PAUL, ABHISHEK; BHAKAT, CHAMPAK; MANDAL, DK; MANDAL, A; MOHAMMAD, A; CHATTERJEE, A; DUTTA, T K (The Indian Journal of Animal Sciences, 2019)
To determine relationship between BCS, ramp fat thickness, body measurements and milk yield, a total of 44 Jersey crossbred cows were observed from calving to 120 days post-partum. The ultrasonography images were recorded from rump region during entire experimental period. Statistically analyzed data revealed that BCS, HG, THT were significantly (P<0.05) less in group 1 than group 2 and group 3. RFT/BFT differences were significant (P<0.05) among 3 groups. More RFT was found in high BCS group followed by medium and low BCS group. The BCS was having strong and significant (P<0.01) correlation with RFT and body weight of animals. The RFT was significantly (P<0.01) correlated with body weight, milk yield, HG, THT and AG. The higher BCS group, lost RFT, BCS and BW faster than other 2 groups to support milk production. It can be concluded that BCS at calving can be used as a reliable criterion in choosing Jersey crossbred cows for higher milk production at organized farm.